Evaluation of physical retrospective dosimetry methods in a realistic accident scenario: Results of a field test. (March 2021) - Discher, Michael; Woda, Clemens; Ekendahl, Daniela; Rojas-Palma, Carlos; Steinhäusler, Friedrich
Abstract: The radiological incident in Cochabamba (Bolivia, 2002), where members of the general public where exposed to an unshielded Ir-192 radiation source whilst traveling on a bus was replicated here in an attempt to asses and evaluate emerging retrospective dosimetry methodologies using objects of daily life, that are either carried on or close to the human body or can be found in the vicinity of an individual. For this purpose an accidental exposure was simulated under controlled conditions in a secured area and an unshielded radioactive source was placed in the cargo compartment of a bus resembling a Radiological Exposure Device (RED). Water canisters and anthropomorphic phantoms were placed at selected seats on the bus and equipped with personal objects (mobile phones, chip cards) that had reference dosimeters attached to them. At one seat position, additional salt dosimeters and dental ceramics in the phantom were also tested. Two types of 8 h exposures were conducted: one with a source activity similar to the one in Cochabamba (0.65 TBq) and one with a stronger source (1.5 TBq) in order to have more samples with absorbed doses above the detection limit of the different methods. For 43 out of 61 resistor and glass samples from mobile phones, measured doses agreed within error limits with reference doses, but for some materials more research is needed for a more reliable application. In 13 cases outliers with a significant dose over- or underestimation were observed, 10 of these could be identified by combining the results of at least three dose assays. The field test thus evaluated the potential and limitation of retrospective dosimetry using personal objects and demonstrated the importance of using a multi-dosimeter approach to increase robustness of the method. Highlights: Evaluation of retrospective dosimetry methods using a radiological exposure device in a bus. Good agreement between measured and reference dose but occasional outliers. Combination of different methods increases robustness.